2020
DOI: 10.3390/microorganisms8050745
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling Using Predictive Biomarkers for the Outcome of Canine Leishmaniasis upon Chemotherapy

Abstract: Prediction parameters of possible outcomes of canine leishmaniasis (CanL) therapy might help with therapeutic decisions and animal health care. Here, we aimed to develop a diagnostic method with predictive value by analyzing two groups of dogs with CanL, those that exhibited a decrease in parasite load upon antiparasitic treatment (group: responders) and those that maintained high parasite load despite the treatment (group: non-responders). The parameters analyzed were parasitic load determined by q-PCR, hemog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Moreover, studies have showed that a higher parasitic load in the canine host is associated with more intense disease, and that these more susceptible dogs are more infectious to the phlebotomine vectors ( 33 , 76 ). Factors such as the parasite's tissue tropism and intrinsic pathophysiological mechanisms make organs such as the spleen more intensely parasitised than other ones in infected dogs ( 77 79 ). Thus, in dogs, the use of samples from such organs is likely to improve diagnostic sensitivity of methods based on the detection of parasites and/or its DNA ( 71 , 75 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies have showed that a higher parasitic load in the canine host is associated with more intense disease, and that these more susceptible dogs are more infectious to the phlebotomine vectors ( 33 , 76 ). Factors such as the parasite's tissue tropism and intrinsic pathophysiological mechanisms make organs such as the spleen more intensely parasitised than other ones in infected dogs ( 77 79 ). Thus, in dogs, the use of samples from such organs is likely to improve diagnostic sensitivity of methods based on the detection of parasites and/or its DNA ( 71 , 75 , 80 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, cross-reactions with other pathogens should be considered, as already reported for dogs ( 83 , 84 ). Susceptible canine hosts develop high antibody levels as the infection progresses, together with the development of clinical alterations and a higher chance to infect vectors ( 66 , 79 , 85 , 86 ). Based on our data, this does not seem to happen in cats.…”
Section: Discussionmentioning
confidence: 99%
“…In dogs, the type of immune response against the parasite also markedly determines whether a dog develops clinical disease or remains in a subclinical stage, and it also strongly affects the prognosis [3,7,9,17,[52][53][54][55][56]. It also seems that some canine breeds present a higher susceptibility to CanL (Boxer, Cocker Spaniel, Rottweiler, and German Shepherd), while the Ibizan Hound is a breed with reported resistance to Leishmania infection [51].…”
Section: Immune Response and Disease Prognosismentioning
confidence: 99%
“…Alongside emerging infection kinetic preemptive models [20], mathematical modeling [21][22][23][24] is increasingly preferred as a non-invasive alternative to experimentation. It has the potential to compare existing strategies and predict future dynamics.…”
Section: Introductionmentioning
confidence: 99%